Histological biomarkers in liver and gills of juvenile Solea senegalensis exposed - Costa, Pedro M. (2009)
Young juvenile Solea senegalensis were exposed to three sediments with distinct contamination profiles collected from a Portuguese estuary subjected to anthropogenic sources of contamination (the Sado estuary, western Portugal). Sedimentswere surveyed formetals (cadmium, chromium, copper, nickel, lead and zinc), ametalloid (arsenic) and organic contaminants (polycyclic aromatic hydrocarbons, polychlorinated biphenyls and a pesticide, dichloro-diphenyl-trichloroethane plus itsmetabolites), aswell as total organic matter, redox potential and particle fine fraction. The fish were exposed to freshly collected sediments in a 28-day laboratorial assay and collected for histological analyses at days 0 (T0), 14 (T14) and 28 (T28). Individual weighted histopathological indices were obtained, based on presence/absence data of eight and nine liver and gill pathologies, respectively, and on their biological significance. Although livers sustained more severe lesions, the sediments essentially contaminated by organic substances caused more damage to both organs than the sediments contaminated by both metallic and organic contaminants, suggesting a possible synergistic effect. Correlation analyses showed that some alterations are linked, forming distinctive histopathological patterns that are in accordance with the severity of lesions and sediment characteristics. The presence of large eosinophilic bodies in liver and degeneration of mucous cells in gills (a first-time described alteration)were some of the most noticeable alterations observed and were related to sediment organic contaminants. Body size has been found to be negatively correlated with histopathological damage in livers following longer term exposures. It is concluded that histopathological indices provide reliable and discriminatory data even when biomonitoring as complex media as natural sediments. It is also concluded that the effects of contamination may result not only from toxicant concentrations but also from their interactions, relative potency and sediment characteristics that ultimately determine bioavailability.